Hybrid Energy Conversion Using Solar Radiation and Temperature Gradient Sources - Avinash Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The increasing need to have clean and sustainable energy has provided the researchers with the desire to look at the hybrid renewal energy systems. A hybrid energy conversion system is discussed in this paper and it integrates sources of solar radiations and temperature gradient to produce power effectively. The solar energy is captured using photovoltaic panels whereas the temperature difference is used through the thermoelectric-generators. Combining the two sources of energy enhances the overall energy efficiency, boosts reliability and minimizes the reliance on one source of renewable energy power. It is applicable to standalone and grid-connected, proposed systems are applicable in high-density regions of solar energy and waste heat. The paper examines the system performance, output energy, and efficiency, which shows the benefits of hybrid energy conversion in today electrical power systems.